If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -7) = 2(x + 7) Reorder the terms: 6(-7 + x) = 2(x + 7) (-7 * 6 + x * 6) = 2(x + 7) (-42 + 6x) = 2(x + 7) Reorder the terms: -42 + 6x = 2(7 + x) -42 + 6x = (7 * 2 + x * 2) -42 + 6x = (14 + 2x) Solving -42 + 6x = 14 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -42 + 6x + -2x = 14 + 2x + -2x Combine like terms: 6x + -2x = 4x -42 + 4x = 14 + 2x + -2x Combine like terms: 2x + -2x = 0 -42 + 4x = 14 + 0 -42 + 4x = 14 Add '42' to each side of the equation. -42 + 42 + 4x = 14 + 42 Combine like terms: -42 + 42 = 0 0 + 4x = 14 + 42 4x = 14 + 42 Combine like terms: 14 + 42 = 56 4x = 56 Divide each side by '4'. x = 14 Simplifying x = 14
| x*x-1=x | | 235+0.75y=125+1.63y | | 36xy-16y= | | 989=11u-(-120) | | 12+(-3x)=3 | | .8w+.4w+.1w=4 | | -10(1.5)+10y=-100 | | 1-ax*2x+1= | | 3m-5=-8(6+5n) | | 2x+33= | | 40=8d | | 3(r-4)=19 | | 3x+5y=-58 | | -3(4p+6)-2(1-14p)=3(3+5p) | | 12+(-3*2)= | | 3z-7=5a+33 | | 9[5-3(x+2)]= | | (1-ax)*(2x+1)= | | 5x+8-12x+6= | | 6n+4=3n+12 | | -15+5z=2+1 | | 17r+8=42 | | -4c=-416 | | 14y+-94=816 | | -18+7x=-x^2 | | -4x^2+6x-(-2)=0 | | 10(-1.5)+10y=-100 | | m*14=175 | | 6t=#(t+4)+t | | 15+8y=3y | | 4x+7y=-80 | | 5p=100 |